Possibility of using compensatory urban drainage techniques as leisure units to expand public areas into subdivisions - Parra, Geovana Geloni (2021)
Many housing estates of social interest have not contributed to implementing leisure areas and reducing their environmental and urban quality. This paper aims to propose a leisure unit using a compensatory urban drainage technique in a housing complex of social interest in the city of São José do Rio Preto, São Paulo, Brazil. The characterization of the area, land use and occupation surveys, area sectorization, and catchment division were carried out. Afterwards, proposals for interventions based on surface runoff were presented using calculations of existing runoff and future scenarios. Results related to environmental and social gains for the area are discussed, as well as the possibility of implementing decentralized compensatory techniques. Moreover, 156 rain gardens and 3 ditches were proposed throughout the subdivisions, which enabled a gain of 989m² of contribution area to infiltrate the whole area, and the use of the retention basin as a leisure area. The total storage volume achieved with the sum of all the techniques implemented was approximately 3,000 cubic meters more than that projected for the existing retention basin.